Tumor volume determination technique using pixel filling and discrete integral function - Aboaba, Abdulfattah A.; Hameed, Shihab Ahmed; Khalifa, Othman Omran; Hassan Abdalla Hashim, Aisha; Harun @ Haron, Rahmat; Mohd Zain, Norzaini Rose (Engineering and Technology Publishing, 2015)
The subject of tumor has generated lots of interest from the medical point of view and recently from engineering/research perspective owing to advancement in medical equipment and increased computerization in many areas including medical field. This paper discusses a post segmentation tumor volume determination technique that employs mainly pixel filling, and the application of discrete integral function to determine tumor volume. The prior steps taken involve finding pixel area resolution, image field of view (FOV), then FFT-Based interpolation to achieve smaller decimation of tumor area, and finally the use of discrete integral function (DIF) to accurately determine tumor volume. The result of the work will enhance the field of oncology in general, and image guided surgery (IGS) in particular.